Improvement of Taxation Competence for MSME Business Actors in Bandung in collaboration with Widyatama University, Bandung Chamber of Commerce and Industry - Dyah Purnamasari; Yati Mulyati; Citra Mariana; Diah Andari; Radhi Radhi; Hafiedh Hafiedh; Yoga Tantular (Warta Pengabdian Andalas, 2024)
This Community Service aims to assist MSME business actors in Bandung in preparing tax reports related to MSMEs, one of which is preparing tax reports related to MSMEs by the rates determined by the latest tax law contained in the harmonization of tax regulations and training in filling out form 1721. The activities were carried out through lectures, discussions, and simulation methods. Participants were very enthusiastic about the explanation and assistance provided by the service team. The output achieved increased the latest taxation knowledge and competence in filling out the annual tax return manually and online. This training was held with the Faculty of Economics and Business, the Widyatama University Accounting Study Program, and the Bandung Chamber of Commerce and Industry. The evaluation results after the implementation showed that the participants expressed satisfaction with the resource persons and the implementation of activities, and the objectives were achieved because the participants gained benefits in the form of knowledge and skills about calculating MSME income tax (PPh) and procedures for filling out form 1721.